Building Healthier Babies & Adults for Tomorrow - May, Linda (Mo Med, 2011)
Current studies intimate the fetal cardiovascular and respiratory systems benefit from exercise throughout pregnancy. These changes persist after birth suggesting that exercise exposure has long-term health benefits lasting into adulthood. Individuals exposed to exercise in utero show no signs of cardiovascular disease (CVD) as adults. Considering the pandemic of CVD in the U.S., these findings suggest further research is warranted concerning the effects of exercise during pregnancy on childhood and adult health outcomes.